2017
DOI: 10.3389/fmicb.2017.00482
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Different Guanine-Plus-Cytosine Content 16S rRNA Genes in Haloarcula hispanica at Different Temperatures

Abstract: The halophilic archaeon Haloarcula hispanica harbors three ribosomal RNA (rRNA) operons (rrnA, rrnB, and rrnC) that contain the 16S rRNA genes rrsA, rrsB, and rrsC, respectively. Although rrsB and rrsC (rrsBC) have almost identical sequences, the rrsA and rrsBC sequences differ by 5.4%, and they differ by 2.5% with respect to guanine-plus-cytosine content (PGC). The strong correlation between the typical growth temperatures of archaea and PGC of their 16S rRNA genes suggests that H. hispanica may harbor differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Haloarcula strains have been isolated from solar salterns and salt lakes in deserts (Juez et al 1986 ; Oren et al 1990 ), where large day-night temperature variations are observed (Wieland et al 2005 ; Sima et al 2013 ; Andrade et al 2015 ; Naghoni et al 2017 ). These strains have two or three copies of rRNA operons ( rrnA , rrnB and rrnC ) in their genomes (Baliga et al 2004 ; Liu et al 2011 ; Ding et al 2014 ; Yun et al 2015 ; Sato et al 2017 ). Each rRNA operon contains a 5S rRNA gene, a 16S rRNA gene ( rrsA , rrsB or rrsC , respectively) and a 23S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Haloarcula strains have been isolated from solar salterns and salt lakes in deserts (Juez et al 1986 ; Oren et al 1990 ), where large day-night temperature variations are observed (Wieland et al 2005 ; Sima et al 2013 ; Andrade et al 2015 ; Naghoni et al 2017 ). These strains have two or three copies of rRNA operons ( rrnA , rrnB and rrnC ) in their genomes (Baliga et al 2004 ; Liu et al 2011 ; Ding et al 2014 ; Yun et al 2015 ; Sato et al 2017 ). Each rRNA operon contains a 5S rRNA gene, a 16S rRNA gene ( rrsA , rrsB or rrsC , respectively) and a 23S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%
“…The 23S rRNA gene sequences show limited diversity (0.3–2%). For 16S rRNA gene sequences, rrsB and rrsC ( rrsBC ) show almost identical sequences, whereas rrsA shows different sequences (4–6%) from rrsBC (Mevarech et al 1989 ; Mylvaganam and Dennis 1992 ; Dennis 1999 ; Sato et al 2017 ). The different sequences of 16S rRNA genes were first reported in Haloarcula marismortui (Mevarech et al 1989 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…GC contents could confound this correlation, because G:C base pairs are linked by three hydrogen interactions, while A:T and A:U base pairs by only two hydrogen bridges. Hence GC contents usually increases with temperature, as it confers higher stability to structures formed by nucleotide chains [188] , [189] , [190] . However, GC codon content does not correlate with body temperature for mitochondria of the above mentioned lepidosaurian species (r = − 0.0425, one-tailed P = 0.379).…”
Section: Whole Organism Properties and Codon Directional Asymmetrymentioning
confidence: 99%